2015
DOI: 10.1093/femsec/fiv063
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of autochthonous soil viral communities parallels dynamics of host communities under nutrient stimulation

Abstract: Viruses are highly abundant in soils with their numbers exceeding those of cooccurring bacterial cells by 10- to over 1000-fold. Water and organic matter content influence the magnitude of the viral-to-bacterial ratio in soils; thus, ecosystem type and land use shape interactions between viral and host microbial communities in soils. Less understood are the shorter term interactions between viral and host communities that ultimately maintain the large viral standing stock within soils. This study examined shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
6
23
0
Order By: Relevance
“…Compositional differences between April and August samples were significant for both viral and microbial communities (Fig 4A), and a Mantel test revealed that the Bray-Curtis dissimilarity matrices of viral and microbial communities were significantly correlated (R = 0.59, P = 0.0003). Unsurprisingly, due to the reliance of viruses on their hosts for replication, viral and microbial communities have been previously observed to correlate in soil (14,18), and results here suggest that viruses and their bacterial and archaeal hosts had coupled temporal responses to the same variables and/or to each other.…”
Section: Viral and Microbial Communities Display Coupled Temporal Dynsupporting
confidence: 61%
See 1 more Smart Citation
“…Compositional differences between April and August samples were significant for both viral and microbial communities (Fig 4A), and a Mantel test revealed that the Bray-Curtis dissimilarity matrices of viral and microbial communities were significantly correlated (R = 0.59, P = 0.0003). Unsurprisingly, due to the reliance of viruses on their hosts for replication, viral and microbial communities have been previously observed to correlate in soil (14,18), and results here suggest that viruses and their bacterial and archaeal hosts had coupled temporal responses to the same variables and/or to each other.…”
Section: Viral and Microbial Communities Display Coupled Temporal Dynsupporting
confidence: 61%
“…Viral replication depends on the successful infection of suitable hosts. As such, the abundances of viral populations and, consequently, the structure of viral communities are inherently linked to the compositional trends of coexisting host communities (18)(19)(20). In agricultural soils, rhizosphere processes can alter microbial diversity by actively promoting or inhibiting the recruitment of select taxa (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the impact of agriculture on soil viral AMGs. We predicted that cultivation would shift the composition of soil viromes due to shifts in soil properties such as pH, total nitrogen content, and fertilizer application, as previously demonstrated 5,6,13,35,36 .…”
Section: Auxiliary Metabolic Genes (Amgs)mentioning
confidence: 87%
“…A global meta-analysis of viral distribution revealed that the vast majority of viruses are clearly habitat-specific 3 . The soil virome in particular is poorly characterized in terms of its size and composition, but limited evidence shows that soil viruses are more abundant and diverse than viruses from other ecosystems 4,5,6 . This high viral diversity may be a result of the heterogeneous physical matrix of soil where spatial structuring generates a plethora of environmental niches 7,8 .…”
mentioning
confidence: 99%
“…Virus abundances in soil have been reported to range between 10 7 and 10 9 virus like particles per g of soil (Williamson et al, 2003 , 2005 ; Swanson et al, 2009 ; Srinivasiah et al, 2015 ) and exceed in some cases (e.g., Antarctic soils) the abundance of co-occurring bacteria by up to 8,200-fold (Williamson et al, 2007 ). So far it is unclear, if, to which degree, and how environmental conditions affect viral numbers and viral community composition in soils.…”
Section: Introductionmentioning
confidence: 99%